INTEGRAL observations of the variability of OAO1657-415 - Barnstedt, J.; Staubert, R.; Santangelo, A.; Ferrigno, Carlo; Horns, Dieter; Klochkov, D.; Kretschmar, Peter; Kreykenbohm, Ingo; Segreto, Alberto; Wilms, Jörn (Astronomy & Astrophysics, 2008)
Context. The Galactic Plane Scan (GPS) was one of the core observation programmes of the INTEGRAL satellite. The highly variable accreting pulsar OAO1657-415 was frequently observed within the GPS.Aims. We investigate the spectral and timing properties of OAO1657-415 and their variability on short and long time scales in the energy range 6-160 keV.Methods. Using standard extraction tools and custom software for extracting INTEGRAL data we analysed energy-resolved light curves with a time resolution of one second-mainly data of the ISGRI instrument. We also analysed phase-averaged broad band spectra -including JEM-X spectra -and pulse-phase resolved spectra of ISGRI.Results. During the time covered by the INTEGRAL observations, the pulse period evolution shows an initial spin-down, which is followed by an equally strong spin-up. In combining our results with historical pulse period measurements (correcting them for orbital variation) and with stretches of continuous observations by BATSE, we find that the long-term period evolution is characterised by a long-term spin-up overlayed by sets of relative spin-down/spin-up episodes, which appear to repeat quasi-periodically on a 4.8 yr time scale. We measure an updated local ephemeris and confirm the previously determined orbital period with an improved accuracy. The spectra clearly change with pulse phase. The spectrum measured during the main peak of the pulse profile is particularly hard. We do not find any evidence of a cyclotron line, wether in the phase-averaged spectrum or in phase-resolved spectra.
Keywords: x-rays : binaries; pulsars : individual : OAO1657-415